Still unseen and ignored: Tracking community knowledge and attitudes about child abuse and child protection in Australia - Tucci, Joseph; Mitchell, Janise (Frontiers in Psychology, 2022)
In September 2003, we released the first results of a national community attitude tracking study about child abuse and child protection (Tucci et al, 2003). At that time, we concluded that as a community, violence against children was tolerated. The community did not understand or appreciate the seriousness, size and cost of child abuse in Australia. There was evidence that child abuse was not viewed as an important challenge facing children in Australia. A second study conducted in 2006 (Tucci et al, 2006) found that nothing much had changed, indeed community engagement with the issue of child abuse may have even deteriorated. A third study in 2010 found that the community actively avoids the problem of child abuse rating it less concerning than high petrol prices. In 2021, eighteen years after the first report was published, we have concluded again that child abuse remains out of sight and out of mind as a community concern. This article describes the findings of this fourth iteration of our survey and analyses the implications for ensuring that individuals are more engaged and committed to taking action to preventing child abuse and/or protecting children from violation.